Profile of Digital Literacy Skills of Class IX Students on Online Learning Mathematics - Nur, Septia; Roza, Yenita; Maimunah, Maimunah (Universitas Negeri Makassar, 2021)
This study aims to determine the profile of digital literacy skills possessed by students in online learning mathematics. This research is a quantitative study. The subjects in this study were students of 9th Grade Imam Syafi'i Junior High School Batam, which may amount to 30 students. The data technique used was a questionnaire, with descriptive data analysis. Based on the research results, it can be seen that the level of digital literacy skills possessed by students is 80% and is in the good category. Where the skill level of each digital literacy indicator, namely internet search skills, was 86% in the very good category, while the hypertext direction guideline skills were 73%, information content evaluation was 82%, and knowledge compilation skills were 82%, the total was in the good category. Furthermore, the results also showed that the most ICT devices used by students in accessing the internet were smartphones 21 students, with 22 students private ownership. The purpose of most students in accessing the internet was to find information 14 students, and the most students accessed in using the internet were academic content 14 students.